Mechanical recanalization in basilar artery occlusion: The ENDOSTROKE study. Issue 3 (13th January 2015) - Singer, Oliver C.; Berkefeld, Joachim; Nolte, Christian H.; Bohner, Georg; Haring, Hans‐Peter; Trenkler, Johannes; Gröschel, Klaus; Müller‐Forell, Wibke; Niederkorn, Kurt; Deutschmann, Hannes; Neumann‐Haefelin, Tobias; Hohmann, Carina; et al.
<x xml:space="preserve">Abstract</x> Objective A study was undertaken to evaluate clinical and procedural factors associated with outcome and recanalization in endovascular stroke treatment (EVT) of basilar artery (BA) occlusion. Methods ENDOSTROKE is an investigator‐initiated multicenter registry for patients undergoing EVT. This analysis includes 148 consecutive patients with BA occlusion, with 59% having received intravenous thrombolysis prior to EVT. Recanalization (defined as Thrombolysis in Cerebral Infarction [TICI] score 2b–3) and collateral status (using the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology collateral grading system) were assessed by a blinded core laboratory. Good (moderate) outcome was defined as a modified Rankin Scale score of 0 to 2 (0–3) assessed after at least 3 months (median time to follow‐up = 120 days). Results Thirty‐four percent had good and 42% had moderate clinical outcome; mortality was 35%. TICI 2b–3 recanalization was achieved by 79%. Age, hypertension, National Institutes of Health Stroke Scale scores, collateral status, and the use of magnetic resonance imaging prior to EVT predicted clinical outcome, the latter 3 remaining independent predictors in multivariate analysis. Independent predictors of recanalization were better collateral status and the use of a stent retriever. However, recanalization did not significantly predict clinical outcome. Interpretation Beside initial stroke severity, the collateral status predicts clinical outcome and recanalization in BA occlusion. Our data suggest that the use of a stent retriever is associated with high recanalization rates, but recanalization on its own does not predict outcome. The role of other modifiable factors, including the choice of pretreatment imaging modality and time issues, warrants further investigation. Ann Neurol 2015;77:415–424